(untitled) (Revista Contexto & Saúde, 2025)
This study aims to analyze the functional health literacy of individuals with spinal cord injury treated at a rehabilitation center. We conducted this analytical cross‑sectional study at a rehabilitation and readjustment center, including 85 individuals diagnosed with spinal cord injury. We collected data on sociodemographic, clinical, and functional profiles. The Short Test of Functional Health Literacy in Adults (S-TOFHLA) was used to assess functional health literacy. Most participants were male, aged between 18 and 39 years, with paraplegia caused by traumatic etiology. Analysis of functional health literacy showed that 70.6% of individuals with spinal cord injury had adequate literacy levels. Better functional health literacy outcomes were associated with younger age, higher income, longer duration of rehabilitation, higher educational levels, and having a partner. In conclusion, the services provided and the organizational structure of reference centers rehabilitating individuals with spinal cord injury may contribute to improved functional health literacy. Identifying related variables and analyzing the functional dimension of health literacy by multidisciplinary teams during rehabilitation are essential tools for enhancing the health outcomes of individuals with spinal cord injury.